PreSERVE-AMI: CD34+ Cells Improve Cardiac Function, Reduce Events after STEMI - Mosley, Mary (MD Conference Express, 2014)
The intracoronary (IC) infusion of bone marrow mononuclear cells after an STEMI improved cardiac function, including left ventricular ejection fraction, infarct size, and end-systolic volume, and major adverse cardiac events. This article discusses the NBS10 (Also Known as AMR-001) Versus Placebo Post ST Segment Elevation Myocardial Infarction trial [PreSERVE-AMI; NCT01495364], which looked at IC autologous CD34+ cell therapy for STEMI patients.